Communication in Graduate Marketability: Barriers or Opportunities? - Saleh, Nor Shela; Mohd Shafie Rosli; Thuaibah Abu Bakar; Azlah Md. Ali (Human Sustainability Procedia, 2021)
This study is a conceptual and literature review in which it explains the significance of communication to prospective graduates in particular as a potential marketability to them. A critical analysis was conducted through this study to look at the two importance’s of communication in graduate marketability, specifically, barriers and opportunities to employment. Based on critical studies, communication will be able to form barriers if graduates do not demonstrate interaction abilities, especially during the interview sessions conducted. On the other hand, communication skills will be an opportunity to marketability if they are able to highlight interaction abilities during the interview session, especially while responding to enquiries modelled by the interviewers. Finally, the university essential improves prospective graduates’ communication abilities at their earlier levels of study in order to figure out some noble communication skills as a marketability opportunity once they graduate from institutions of higher learning, whether in the public or private sector.